Stroke Disability and Physiotherapy Interventions: A Quantitative Evaluation of Physiotherapy Treatment Approaches in Zambia - Mpemba, Muatle; Shula, Hstings Kachingwe; Chiluba, Brian Chanda (Indonesian Journal of Disability Studies, 2020)
As a result of physical disability after stroke, most of the patients need physiotherapy. Due to different backgrounds, knowledge, clinical experiences, personal preferences, and continually developing clinical practices, physiotherapists use different methods to treat their stroke patients. This study was designed to determine physiotherapists' perspective on the physiotherapy interventions for stroke patients at the University Teaching Hospital and Levy Mwanawasa University Teaching Hospital in Lusaka. This was a cross-sectional study. Data was collected through a standardized questionnaire with modifications to fit the scope of the study. A total of 36 participants consisting of 23 Physiotherapists and 13 physiotherapy Technologists was considered. The data obtained was analyzed by using descriptive analysis and chi-square test was used to test the association. The results showed that PNF/Brumstrom (92%) was the most taught approach among the respondents in their professional education. The preferred treatment approaches in stroke rehabilitation which are used by Physiotherapists and physiotherapy Technologists are repetitive functional task practice (72%), motor learning (69%) and PNF/Brumstrom (67%). There is need to incorporate the newer physiotherapy treatment approaches into the physiotherapy practice as the scope of practice that reflects the latest evidence base improves the provision of services and contributes to better and cost-effective physiotherapy interventions for stroke patients.